Pendekatan Berpusatkan Murid dalam Pengintegrasian Ilmu bagi Subjek Pendidikan Islam - Deena Bibi Nurkiah binti Hasmadi; Mohd Aderi Che Noh; Ali Rohmad (Jurnal Pendidikan Nusantara, 2022)
The student-centred approach is an educational transformation that maximizes student engagement in pdp sessions. It is important to achieve learning objectives in addition to increasing the level of students' knowledge of a topic being discussed. The objective of this study is to identify the concept of a student-centered approach including definitions, interests and examine examples of student-centered applications in integrating knowledge for the subject of Islamic Education. This study was carried out qualitatively where the study was carried out in a library manner. The results show that the student-centered approach gives a positive impression in integrating knowledge for the subject of Islamic Education and among the activities that can be carried out are cooperative learning, learning through problem solving, brief notes and regular exercises.